Blood in the Water - Jackson, Tiffany D. (New York : Scholastic Inc., 2025)
"Brooklyn girl Kaylani McKinnon is thrust into an intricate web of lies when a shocking murder on Martha's Vineyard threatens to expose dangerous secrets"--.
new kids book 2025 summer.
Ages 9-12.
Grades 4-6.
Keywords: Secrets -- Fiction; African Americans -- Fiction; Mystery and detective stories; Secrecy; Novels; Murder -- Fiction; Martha's Vineyard (Mass.) -- Fiction; Detective and mystery fiction; Novels; Detective fiction; Mystery fiction